Domestic Horse Bite: An Unusual Etiology of Crush Injury of the Fourth Finger—How to Manage? - Naoufal Elghoul; Youssef Jalal; Ayoub Bouya; Ali Zine; Abdeloihab Jaafar (Case Reports in Infectious Diseases)
Almost 2% of all emergency admissions involve an animal bite. While horses bite humans very rarely, their bites are mostly associated with fatalities. Herein, we report the case of a 23-year old bitten by a domestic horse causing a crush injury to his fourth finger with fracture dislocation of the proximal interphalangeal joint. The patient benefited upon arrival at the emergency department from copious irrigation with saline serum, tetanus toxoid, postexposure rabies vaccination, and prophylactic antibiotic therapy. In the operating room, surgical exploration found the ulnar digital pedicle sectioned, the flexor and extensor tendons sectioned and shredded, and the skin shredded. An excisional debridement of devitalized tissue with copious irrigation was performed, and the finger regularized at the level of traumatic amputation with tendon striping followed by coverage of the bone by the radial digital flap with careful clinical and biological monitoring after the surgery. At the last follow-up, the patient revealed no sign of infection, and he returned to his usual activities and has been discharged from care. This wound management, based on a careful examination, a meticulous debridement, and an efficient cleaning with early and targeted antibiotic therapy, might promote good results and avoid dangerous complications.